Afghanistan - Scoping Strategic Options for Development of the Kabul River Basin : A Multisectoral Decision Support System Approach - World Bank (Washington, DC, 2014)
The objective of this study is to develop an integrated basin planning framework for analyzing and prioritizing water resources development options in Afghanistan, and to demonstrate its application in the Kabul River basin. Accordingly, the study focuses on the tasks of: (a) analyzing the medium and long-term options for developing the water resources of the Kabul River basin for multiple purposes, including domestic and industrial water supply, hydropower, mining, irrigated agriculture, and environment; and (b) collating information on the basin, including the existing and potential water resources development options, water uses and demands, in a simple and user-friendly Decision Support System (DSS), so as to enable multisectoral analysis and optimization of development options in the basin by the concerned ministries and development partners. The study, conducted in collaboration with the government of Afghanistan, is expected to help strengthen the adoption of integrated approaches to basin planning and water resources management in the country.